The Efficiency and Effectiveness of Tax Audit From the Perspective of Self Assessment Requirements Conditions and Advantages. (Al-Mansour Journal, 2022)
This paper aimed at focusing on the tax audit’s efficiency and effectiveness which is considered as a tool of self assessment’s requirements demanded radical change for both tax administration and the taxpayers in order to realize self assessment objectives such as increasing of tax audit’s efficiency and effectiveness, tax reviewer, tax revenues and tax equality.
Keywords: Self assessment system; Tax Audi; Voluntary compliance